Tetraspanin CD9 Limits Mucosal Healing in Experimental Colitis - Saiz, María Laura; Cibrian, Danay; Ramírez-Huesca, Marta; Torralba, Daniel; Moreno-Gonzalo, Olga; Sánchez-Madrid, Francisco (Frontiers in Immunology, 2017)
Tetraspanins are a family of proteins with four transmembrane domains that associate between themselves and cluster with other partner proteins, conforming a distinct class of membrane domains, the tetraspanin-enriched microdomains (TEMs). These TEMs constitute macromolecular signaling platforms that regulate key processes in several cellular settings controlling signaling thresholds and avidity of receptors. In this study, we investigated the role of CD9, a tetraspanin that regulates major biological processes such as cell migration and immunological responses, in two mouse models of colitis that have been used to study the pathogenesis of inflammatory bowel disease (IBD). Previous in vitro studies revealed an important role in the interaction of leukocytes with inflamed endothelium, but in vivo evidence of the involvement of CD9 in inflammatory diseases is scarce. Here, we studied the role of CD9 in the pathogenesis of colitis in vivo. Colitis was induced by administration of dextran sodium sulfate (DSS), a chemical colitogen that causes epithelial disruption and intestinal inflammation. CD9−/− mice showed less severe colitis than wild-type counterparts upon exposure to DSS (2% solution) and enhanced survival in response to a lethal DSS dose (4%). Decreased neutrophil and macrophage cell infiltration was observed in colonic tissue from CD9−/− animals, in accordance with their lower serum levels of TNF-α, IL-6, and other proinflammatory cytokines in the colon. The specific role of CD9 in IBD was further dissected by transfer of CD4+ CD45RBhi naive T cells into the Rag1−/− mouse colitis model. However, no significant differences were observed in these settings between both groups, ruling out a role for CD9 in IBD in the lymphoid compartment. Experiments with bone marrow chimeras revealed that CD9 in the non-hematopoietic compartment is involved in colon injury and limits the proliferation of epithelial cells. Our data indicate that CD9 in non-hematopoietic cells plays an important role in colitis by limiting epithelial cell proliferation. Future strategies to repress CD9 expression may be of therapeutic benefit in the treatment of IBD.